The Effect Of Overhand Passing Training Using (Wall Bounce) On The Accuracy Of Overhand Passing Skills In Volleyball - Sari, Felinda; Armanjaya, Satria; Ramadhan, Ziko Fajar; Renaldi, Renaldi; Iksan, Khoiril (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Objectives. The purpose of this study is to analyze the effect of overhand passing training using a wall target (wall bounce) on improving overhand passing skills in volleyball. Materials and Methods: This study employed an experimental method. Data were collected through pre-test and post-test. The sample consisted of undergraduate students from the Physical Education program at Universitas Aisyah Pringsewu, selected randomly. The overhand passing accuracy test served as the research instrument. Results: The average results of the study showed that the pre-test accuracy score for overhand passing was 26.25, while the post-test average score increased to 33.7. In the pre-test, the calculated t-value was 21.000, which is greater than the t-table value of 1.859. Similarly, in the post-test, the calculated t-value was 18.445, which also exceeded the t-table value of 1.859. These results indicate a significant effect. Therefore, it can be concluded that overhand passing training using a wall target has a significant impact on the accuracy of overhand passing skills in volleyball among undergraduate Physical Education students at Universitas Aisyah Pringsewu.